1998
DOI: 10.1002/(sici)1096-8628(19980501)77:2<155::aid-ajmg9>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The facioscapulohumeral muscular dystrophy (FSHD1) gene affects males more severely and more frequently than females

Abstract: We investigated 52 families of patients with facioscapulohumeral muscular dystrophy (FSHD1), including 172 patients (104 males and 68 females). Among 273 DNA samples which were analyzed with probe p13E-11, 131 (67 males and 64 females) were shown to carry an EcoRI fragment smaller than 35 kb; 114 among them were examined clinically and neurologically. Results of the present investigation showed that: a) there is no molecular evidence for autosomal or X-linked recessive inheritance of FSHD1; b) an excess of aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 20 publications
5
74
1
2
Order By: Relevance
“…An excess of affected men has been reported for other autosomal Electronic letter dominant neurological disorders such as myotonic dystrophy, 32 33 Machado-Joseph disease or SCA3 cerebellar ataxia, 34 DRPLA, 35 and more recently facioscapulohumeral muscular dystrophy (FSHMD). 36 For SCA3, myotonic dystrophy, and DRPLA it has been suggested that the excess of affected males could be explained by meiotic drive favouring the transmission of enlarged alleles. However, in the case of FSHMD, DNA analysis showed that the proportion of men and women carrying the deleted abnormal EcoRI/BlnI allele was the same, thus suggesting other mechanisms to explain why women were less often or more mildly affected than men.…”
Section: Discussionmentioning
confidence: 99%
“…An excess of affected men has been reported for other autosomal Electronic letter dominant neurological disorders such as myotonic dystrophy, 32 33 Machado-Joseph disease or SCA3 cerebellar ataxia, 34 DRPLA, 35 and more recently facioscapulohumeral muscular dystrophy (FSHMD). 36 For SCA3, myotonic dystrophy, and DRPLA it has been suggested that the excess of affected males could be explained by meiotic drive favouring the transmission of enlarged alleles. However, in the case of FSHMD, DNA analysis showed that the proportion of men and women carrying the deleted abnormal EcoRI/BlnI allele was the same, thus suggesting other mechanisms to explain why women were less often or more mildly affected than men.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly intriguing, as recent studies have demonstrated that the clinical expression of the disease may become more severe as the condition is passed from one generation to the next. 1,39,47,48 Despite the unequivocal association of the 4q35 short fragment with FSHD, the precise gene or genes affected by this defect have remained unknown. Despite an intensive search over the past 8 years, no genes have been identified in the 4q35 deleted region, a region that includes telomeric heterochromatin, which is usually not transcribed.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…A relationship has been established between the severity of the disease and the percentage of peripheral blood lymphocytes (PBL) carrying the FSHD allele in combination with the residual repeat size . It has been reported, by these researchers and others, (Kohler et al 1996;Upadhyaya et al 1995;Zatz et al 1998) that a significant proportion of FSHD mosaic carriers are asymptomatic. However, it is not known if this occurs because the mosaicism is unequally distributed between different tissues and that in some cases, muscle is relatively spared for the presence of the disease allele or due to a mechanism that has not been identified yet.…”
Section: Introductionmentioning
confidence: 78%